Neuronal melatonin type 1 receptor overexpression promotes M2 microglia polarization in cerebral ischemia/reperfusion-induced injury. (31st January 2023) - Suofu, Yalikun; Jauhari, Abhishek; Nirmala, Emilia S.; Mullins, William A.; Wang, Xiaomin; Li, Fang; Carlisle, Diane L.; Friedlander, Robert M.
Highlights: Melatonin induced long-term neuroprotection after cerebral ischemia may be mediated, at least in part, by a shift away from inflammatory M1 microglia and towards the protective properties of M2 microglia. Both the protective microglia polarization and resulting neuroprotection are mediated at least in part by neuronally expressed MT1 receptor. Abstract: Microglial activation is readily detected following cerebral ischemia/reperfusion-induced injury. Activated microglia polarize into either classic pro-inflammatory M1 or protective M2 microglia following ischemia/reperfusion-induced injury. Melatonin is protective immediately after ischemia/reperfusion-induced brain injury. However, the ability of melatonin to affect longer-term recovery from ischemic/reperfusion-induced injury as well as its ability to modulate microglia/macrophage polarization are unknown. The goal of this study is to understand the impact of melatonin on mice 14 days after injury, as well as to understand how melatonin affects microglial polarization of neuronal MT1 activation following cerebral ischemia/reperfusion. We utilized NSE MT1 -GFP transgenic mice which overexpress MT1 (melatonin type 1 receptor) in neurons. Melatonin-treated or vehicle treated wild type and NSE MT1 -GFP mice underwent middle cerebral artery occlusion (MCAO)/reperfusion and followed for 14 days. Neuronal MT1 overexpression significantly reduced infarct volumes, improved motor function, and ameliorated weight loss. Additionally, melatonin treatment reduced infarct volume in NSE MT1 -GFP mice as compared to untreated wild type, melatonin treated wild type, and untreated NSE MT1 -GFP mice. Melatonin improved neurological function and prevented weight loss in NSE MT1 -GFP mice compared with melatonin treated wild type mice. Finally, melatonin treatment in combination with MT1 overexpression reduced the numbers of Iba1 + /CD16 + M1 microglia and increased the numbers of Iba1 + / CD206 + M2 microglia after ischemic injury. In conclusion, neuronal MT1 mediates melatonin-induced long-term recovery after cerebral ischemia, at least in part, by shifting microglial polarization toward the neuroprotective M2 phenotype.